Aperture and Suspensory Fixation Equally Efficacious for Quadriceps Tendon Graft Fixation in Primary ACL Reconstruction: A Systematic Review - Crum, Raphael J.; de SA, Darren; Kanakamedala, Ajay C.; Obioha, Obianuju A.; Lesniak, Bryson P.; Musahl, Volker (The Journal of Knee Surgery, 2020)
This review is aimed to compare suspensory and aperture quadriceps tendon autograft femoral and tibial fixations in primary anterior cruciate ligament reconstruction (ACL-R), and the clinical outcomes and complication profiles of each fixation method. Greater understanding of the optimal graft fixation technique for quadriceps tendon (QT) autografts may assist surgeons in improving outcomes after ACL-R. PubMed, Embase, and Medline were searched from database inception to September 2017, and again to July 2018, and identified 3,670 articles, 21 studies of which satisfied inclusion/exclusion criteria. Across included studies, 1,155 QT ACL-R patients (mean age, 28.7 years [range, 15–59 years], with mean postoperative follow-up of 36.1 months [range, 3.4–120 months]), were analyzed. Suspensory fixation on both sides demonstrated a higher percentage of patients (81.7%) achieving the highest rating of “A or B” on the International Knee Documentation Committee (IKDC) knee ligament examination form compared with aperture fixation on both sides (67.7%). Moreover, suspensory fixation had a lower side-to-side difference in anterior laxity (1.6 mm) when compared with aperture fixation (2.3 mm). Among studies which reported graft failure, all of which employed aperture fixation, the rate was 3.2%. Across available data, primary ACL-R using QT grafts appears to have successful short-term outcomes with a short-term graft failure rate of 3% independent of fixation method. While there is limited data regarding the comparison of aperture and suspensory soft-tissue quadriceps tendon (SQT) fixation in ACL-R, the findings of this systematic review suggest that suspensory fixation and aperture fixation in both the femoral and tibial tunnels are equally efficacious based on clinical outcome data on IKDC grade and measured laxity. This is a level IV, systematic review study.
Keywords: anterior cruciate ligament; quadriceps tendon; graft fixation